THEORY OF EVIDENCE – THE METHODOLOGICAL BASIS OF DOCUMENTING AND INVESTIGATING ESPIONAGE - Попихач , Д. К. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2023)
Abstract. The article is devoted to a comprehensive analysis of methodological approaches to the documentation and investigation of espionage. The focus is on the theory of evidence as a fundamental tool that ensures the systematic and scientific validity of the collection and use of evidence in espionage cases. The purpose of the article is to determine the role of the theory of evidence in the documentation of espionage activities and to develop recommendations for increasing the effectiveness of counterintelligence, operational and investigative activities and pre-trial investigation of such crimes. It is proved that espionage poses a direct threat to national security, and the successful exposure and evidence of this latent crime contributes to the strengthening of state security and the rule of law in the field of countering intelligence and sabotage attacks. The article proposes scientifically sound approaches that allow law enforcement agencies to more effectively detect and document espionage activities in the context of modern security challenges. It is emphasized that a successful investigation of espionage requires a clear definition of the subject of proof – a set of facts that must be established to prove guilt in espionage (in particular, the fact of illegal collection or transmission of information constituting a state secret, the suspect’s connection with foreign intelligence, intent to harm the state, etc.). The theory of proof offers a system of principles according to which each of these elements must be confirmed by proper and admissible evidence. In the process of investigating espionage, such a theoretical basis helps investigators systematically put forward and verify investigative versions, avoid randomness in collecting evidence, and ensure their proper procedural formality. As a result, adherence to scientific approaches to proof increases the likelihood of successful disclosure of the crime and a guilty verdict that is resistant to possible appeals in court. The work details the main methods of collecting, verifying, and evaluating evidence in espionage cases that arise from the theory of proof. It is noted that the collection of evidence in such cases has its own specifics due to the high level of secrecy of criminal activity. Special attention is paid to the specifics of documenting acts of espionage as an integral part of the process of proving. Documentation is understood as recording the revealed facts of illegal activity in the procedural form prescribed by law so that such facts acquire the status of evidence. The article notes that due to the conspiratorial nature of espionage, its documentation is inextricably linked with the conduct of counterintelligence and operational-search measures. The article concludes with an emphasis on the fact that only the synergy of science and practice – the introduction of modern theory of evidence into the daily activities of law enforcement agencies – will ensure the inevitability of punishment for espionage and the protection of the national security of Ukraine.

Анотація. Стаття присвячена комплексному аналізу методологічних підходів до документування та розслідування шпигунства. У центрі уваги – теорія доказування як фундаментальний інструмент, що забезпечує системність і наукову обґрунтованість збирання та використання доказів у справах про шпигунство. Метою статті є визначення ролі теорії доказування у документуванні шпигунської діяльності та вироблення рекомендацій для підвищення ефективності контррозвідувальної, оперативно-розшукової діяльності та досудового розслідування таких злочинів. Доводиться, що шпигунство становить пряму загрозу національній безпеці, а успішне викриття і доказування цього латентного злочину сприяє зміцненню державної безпеки та верховенства права у сфері протидії розвідувально-диверсійним посяганням. У статті пропонуються науково обґрунтовані підходи, які дозволяють правоохоронним органам ефективніше виявляти та документувати шпигунську діяльність в умовах сучасних безпекових викликів. Наголошується, що успішне розслідування шпигунства потребує чіткого визначення предмета доказування – сукупності фактів, які необхідно встановити для доведення вини у шпигунстві (зокрема, факт незаконного збору або передачі інформації, що становить державну таємницю, зв’язок підозрюваного з іноземною розвідкою, умисел на шкоду державі тощо). Теорія доказування пропонує систему принципів, за якими кожен з цих елементів має бути підтверджений належними і допустимими доказами. У процесі розслідування шпигунства така теоретична база допомагає слідчим планомірно висувати і перевіряти слідчі версії, уникати випадковості при зборі доказів та забезпечувати їхню належну процесуальну оформленість. В результаті, дотримання наукових підходів доказування підвищує ймовірність успішного розкриття злочину і обвинувального вироку, стійкого до можливих оскаржень у суді. У роботі докладно висвітлено основні методи збирання, перевірки та оцінки доказів у справах про шпигунство, що випливають з теорії доказування. Зазначається, що збирання доказів у таких справах має свою специфіку через високий рівень секретності злочинної діяльності. Окрему увагу приділено специфіці документування актів шпигунства як невід’ємної складової процесу доказування. Під документуванням розуміється фіксація виявлених фактів протиправної діяльності у передбаченій законом процесуальній формі, щоби такі факти набули статусу доказів. У статті відзначається, що через конспіративний характер шпигунства його документування нерозривно пов’язане з проведенням контррозвідувальних та оперативно-розшукових заходів. Стаття завершується акцентом на тому, що лише синергія науки і практики – впровадження сучасної теорії доказування в щоденну діяльність правоохоронних органів – забезпечить невідворотність покарання за шпигунство та захист національної безпеки України.
ТЕОРІЯ ДОКАЗУВАННЯ – МЕТОДОЛОГІЧНА ОСНОВА ДОКУМЕНТУВАННЯ І РОЗСЛІДУВАННЯ ШПИГУНСТВА
Keywords: theory of evidence; espionage; digital forensics; documentation; investigation; subject of evidence; information technologies; state security.; теорія доказування; шпигунство; цифровий форензик; документування; розслідування; предмет доказування; інформаційні технології; державна безпека.